2020
DOI: 10.3390/jof6040363
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Response of Macrophages THP-1 during Co-Culture with Inactive Trichophyton rubrum Conidia

Abstract: Trichophyton rubrum is causing an increasing number of invasive infections, especially in immunocompromised and diabetic patients. The fungal invasive infectious process is complex and has not yet been fully elucidated. Therefore, this study aimed to understand the cellular and molecular mechanisms during the interaction of macrophages and T. rubrum. For this purpose, we used a co-culture of previously germinated and heat-inactivated T. rubrum conidia placed in contact with human macrophages cell line THP-1 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Moreover, Trichophyton rubrum is an opportunistic pathogen responsible for progressively expanding invasive diseases. NGS technology targeting microRNAs showed that the inactivated germinated T. rubrum microconidia co-cultured with human macrophages promoted the release of proinflammatory cytokines and changes in the regulation of microRNAs [ 31 ]. In addition, the group led by Ana Lúcia Fachin co-cultured T. rubrum CBS 118892 with human keratinocytes to assess the efficacy of terbinafine, a medicine used to treat dermatophyte infections [ 32 ].…”
Section: Ngs and Fungal Sequencingmentioning
confidence: 99%
“…Moreover, Trichophyton rubrum is an opportunistic pathogen responsible for progressively expanding invasive diseases. NGS technology targeting microRNAs showed that the inactivated germinated T. rubrum microconidia co-cultured with human macrophages promoted the release of proinflammatory cytokines and changes in the regulation of microRNAs [ 31 ]. In addition, the group led by Ana Lúcia Fachin co-cultured T. rubrum CBS 118892 with human keratinocytes to assess the efficacy of terbinafine, a medicine used to treat dermatophyte infections [ 32 ].…”
Section: Ngs and Fungal Sequencingmentioning
confidence: 99%
“…Other reports have described the morphological and ultrastructural modifications of T. rubrum hyphal cells that were treated with different antifungal agents. These include ME1111, which exerted its antifungal action through interfering with active transport system found in the cell membrane with subsequent cell lysis [ 60 ], and K101 nail solution, which disrupted the contact between the cell wall and the inner membrane [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies suggested that PPARγ could partly regulate the level of the NF-κB signaling pathway. NF-κB signaling pathway activation may be the control point for the expression of abundant inflammatory response genes ( 49 ). In the present study, rosiglitazone inhibited NF-κBp65 phosphorylation and increased IKBα expression, reversing LPS-induced activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%